(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This scientific paper sheds light on four heritage villages in Southern Jordan: Village of Dana in Bsaira District in Tafileh Governorate, Village of Taybeh (TaybeT Zaman), Village of Khirbet Al-Nawafilah (Beit Zaman), and Village of Aljay in Petra District in Ma’an Governorate. These villages were developed and invested by the private sector until they became distinct tourist attractions by employing their urban heritage within the services offered to tourists both internally and externally. In a short period of time, the tourism activities in these heritage villages became one of the most important and major economic resources that contributed to the development of communities and local institutions. Both local people and investors benefited alike.